A bibliographic review of the difficulties related to the topics of mechanics - André da Silva Ramos de Faria; Márcio Velloso da Silveira; Antonio Carlos Fontes dos Santos (Education and Development Research, 2025)
This paper presents a literature review on the difficulties faced by students in Mechanics, carried out by consulting articles in journals, dissertations, and theses that address the subject. The research method used is a Systematic Literature Review (SLR) and the research focuses on publications in physics education, covering the first records on the subject, at the end of the 1970s, with a main emphasis on studies carried out in the last ten years and excluding the rarely cited older articles. The works found were selected because they were: highly cited articles, review articles, and recent articles in the main journals in the area (last ten years) and organized into four categories: i) spontaneous conceptions, ii) conceptual resources used by students, iii) constructivist methods and iv) engagement methods. In the works identified, it was found, for example, that there is a significant amount of publications that explore the subject, but a consolidated solution has not yet been observed. Furthermore, it is clear that the traditional methods of teaching physics contribute little to the understanding of basic concepts and that there is a shortage of studies that propose practical solutions to the problems experienced by physics teachers working in high schools. The research concentration is with higher education students, without a progressive development to address this problem from high school onwards.